Chamois leather tanning accelerated by oxidizing agent of Hydrogen Peroxide - Ono Suparno; E Gumbira Sa’id; Ika A Kartika; M Muslich; Shiva Amwaliya (ASOSIASI PENDIDIKAN TINGGI TEKNIK KIMIA INDONESIA (APTEKIM), 2012)
A weakness of chamois leather production practiced nowadays is its oxidation process taking relatively long time, i.e. nine days to two weeks. The use of an oxidizing agent was reported to shorten the oxidation process of the tanning. Appropriate condition for the tanning needs to be applied in order to improve the process efficiency and to obtain satisfactory quality leather. In this study, the best oxidation times inside and outside the rotary drum of the tanning accelerated by hydrogen peroxide were investigated. The experiment was conducted by tanning of pickled goatskin for 4, 6, and 8 hours oxidation times inside the rotary drum and 1, 2, and 3 days of oxidation times outside the drum. The physical and organoleptic properties of the leathers were tested. The physical and organoleptic properties of the leathers resulted by this study met the quality requirements for the chamois leather. The best conditions for the tanning were oxidation times of eight hours inside the rotary drum and one day outside the rotary drum. Keywords: acceleration, chamois leather, hydrogen peroxide, oxidation time, rubber seed oil, tanningAbstrakKelemahan dari produksi kulit samoa yang dipraktekkan saat ini adalah proses oksidasinya yang memerlukan waktu yang relatif lama, yaitu sembilan hari sampai dua minggu. Penggunaan bahan pengoksidasi dilaporkan dapat mempersingkat proses oksidasi pada penyamakan tersebut. Kondisi yang sesuai untuk penyamakan tersebut diperlukan untuk meningkatkan efisiensi proses dan untuk mendapatkan kulit samak bermutu tinggi. Dalam studi ini, diteliti waktu oksidasi terbaik di dalam dan di luar drum berputar pada penyamakan kulit samoa yang dipercepat menggunakan hidrogen peroksida. Penelitian dilakukan dengan menyamak kulit pikel kambing selama 4, 6, dan 8 jam waktu oksidasi di dalam drum berputar dan 1, 2, dan 3 hari waktu oksidasi di luar drum. Sifat-sifat fisik dan organoleptik dari kulit samak diuji. Sifat-sifat fisik dan organoleptik dari kulit samoa yang dihasilkan dari peneltian ini memenuhi persyaratan mutu kulit samoa. Waktu oksidasi terbaik adalah delapan jam oksidasi di dalam drum berputar dan satu hari oksidasi di luar drum berputar.Kata kunci: percepatan, kulit samoa, hidrogen peroksida, waktu oksidasi, minyak biji karet, penyamakan